1999
DOI: 10.12693/aphyspola.96.245
|View full text |Cite
|
Sign up to set email alerts
|

Muon Spin Rotation Studies of the Vortex Matter in the High-TcSuperconductor Bi2Sr2CaCu2O8+δ

Abstract: We report muon spin rotation studies of the magnetic field distribution n(B) in the vortex state of the high-temperature superconductor Bi2 Sr2 CaCu2 O8+δ. From our data on three sets of overdoped, nearly optimized and underdoped smgle crystals we obtain evidence for a two-stage melting process of the vortex matter under equilibrium. conditions. In the irreversible regime well below the irreversibility line we observe a transition in the vortex state which we associate with an intra-planar melting transition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The overall behaviour presented in figure 13 is also qualitatively similar to the phase diagrams of vortex matter observed in disordered high-T c superconductors, where close to the critical temperature, the SMP and/or PE lines are positioned very close to the irreversibility line [4,[17][18][19][59][60][61]. A quantitative comparison to recently proposed theoretical models could give further information for the underlying mechanisms that motivate the observed similarity.…”
Section: Phase Diagram Of Vortex Matter For Nb-2 Comparison With Theo...supporting
confidence: 76%
“…The overall behaviour presented in figure 13 is also qualitatively similar to the phase diagrams of vortex matter observed in disordered high-T c superconductors, where close to the critical temperature, the SMP and/or PE lines are positioned very close to the irreversibility line [4,[17][18][19][59][60][61]. A quantitative comparison to recently proposed theoretical models could give further information for the underlying mechanisms that motivate the observed similarity.…”
Section: Phase Diagram Of Vortex Matter For Nb-2 Comparison With Theo...supporting
confidence: 76%
“…If the decoupling transition for the crystal with T c = 89.9 K occurs at the points defined at T 1 , the melting transition can be located on the same line (as in the case of the highly anisotropic BSCCO compound [9,[56][57][58][59]) or at the endpoint T 2 of the fishtail peak in agreement to the two-stage melting scenario [1,37]. Similar behaviour has also been observed in the case of less anisotropic YBCO [60][61][62] and BSCCO [63][64][65] crystals.…”
Section: Melting Line In a Layered Superconductorsupporting
confidence: 69%
“…This effect, although less pronounced, can be observed even at the temperature of 49.8 K. However, at this temperature E 0 /2T = 0.6625, which is about twice as large than at 39.8 K. Unfortunately, the model of Koshelev and Bulaevskii [14] does not take into account the appearance of sub-phases of vortex matter within the vortex-liquid state, i.e. of the flux-line liquid and pancake-gas, as proposed later by Blasius et al [11,12], which could explain the behaviour of B b and B r shown in figure 4.…”
Section: Resultsmentioning
confidence: 90%
“…According to Vinokur et al [10], the vortex-phase diagram of Bi 2 Sr 2 CaCu 2 O 8+δ in the B-T plane usually consists of three distinct phases: the vortex-solid phase stable over the entire temperature range below the critical temperature T c for small magnetic fields, the vortex-glass phase, stable at low temperatures, below approximately 0.5 T c and higher magnetic fields, and the remaining vortex-liquid phase, for temperatures above approximately 0.5 T c and higher magnetic fields than the vortex-solid phase. Two other possible vortex phases within the vortex-liquid phase have been proposed by Blasius et al: the flux-line liquid and pancake-gas phase [11,12].…”
Section: Introductionmentioning
confidence: 99%